Development of System Tracer of Lost Aircraft - Siswayudi Azhari (Institute of Advanced Engineering and Science, 2016)
Today the world has entered the era of modern air transport where human movement needed to support facilities and infrastructure that support for the movement of activity. The number of routes and flights are always growing by leaps and bounds every year.In Indonesia alone by more than 10 of the largest airliner in which two, namely Garuda Indonesia and Lion Airline, based on data in 2012 each have no less than 50 routes per day and more than 4,000 flights per week [1] (web magazine ZonaAero). To support the security and safety of air transport, the government through the aviation authorities are trying to build an adequate infrastructure. A number of local governments and central government together with Angkasa Pura and Airnav Indonesia (LPPNPI) has a lot to develop the airport terminal, lengthen and widen the runway, install instrument flight (radar, DVOR, ILS etc.), and make the regulations more guarantees The good level of a security and aviation safety.However, for things that are not desirable that may occur as aircraft accidents, it is necessary to support the system also prepared to facilitate the search for the location of the accident. Still clear in our memory how when, on May 9, 2012 a plane Sukhoi Superjet 100 has crashed in the promotion and demonstration flights. It takes more than one day to find the crash site in the area around Mount Salak located less than 100 kilometers from the capital city of Jakarta [2] (Indonesia Wikipedia).The distance of time ranging from a loss of communication with the aircraft until the discovery of the accident scene will be very good if it can be reduced to as small as possible. This will help Basarnas and NTSC accelerate the process of investigation and to provide certainty for the families of the victims as well as those of other interested parties.Location tracking system of aircraft accident would be able to find the location of a plane crash just a few moments after the breakdown of communication between the aircraft control tower / flight controller.